Produtividade da Soja em função da velocidade de semeadura no Sul do Tocantins - Cardozo, Rafael Galvão (Universidade Federal do Tocantins, 2021)
Sowing is one of the operations that most influence the grain production system, requiring special attention in this operation for the success of production. The aim of the present study was to evaluate the direct influence of sowing speed on the final soybean productivity in the southern of Tocantins. The experiment was carried out at farm Renascer, Cariri do Tocantins - TO. The experimental design was carried out in randomized blocks, with five treatments. The factors studied were five sowing speeds, (4, 5, 6, 7 and 8 km h-1). The measured variables were: grain productivity in sc ha-1, percentage of double plants and percentage of failures. In the studied conditions, the increase in the displacement speed in the sowing operation had a negative influence on the productivity, also occurring an increase in the percentage of double plants and failures, despite not obtaining a minimum significant difference in these last two variables. The increase in the speed of movement of the seeder interfered in the number of seeding failures. The highest productivity was obtained with the displacement speed of the sower of 4 km h-1.